Portugal : 2006 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Portugal. (IMF Staff Country Reports; Country Report, 2006)
Important progress can be seen in the economic and policy environment in Portugal, but challenges remain. Firm implementation of strategy is essential to meet these challenges. It will be essential that expenditure measures move to the forefront, realizing the planned shift away from revenue-based adjustment. Fiscal adjustment will be needed to ensure long-term sustainability. A credible deficit reduction strategy is essential to raise potential growth. The financial system is sound and well supervised, but the government should continue to monitor risks closely.